Platinum-free counter electrodes of plasma-modified hybrid nanomaterials for dye-sensitised solar cells. Issue 7 (9th August 2018) - Erten-Ela, Sule; Kiristi, Melek; Varlec, Ana; Bozduman, Ferhat; Remskar, Maja; Oksuz, Lutfi; Oksuz, Aysegul Uygun
ABSTRACT: Molybdenum disulphide (MoS2 ) nanotube and tungsten oxide (W18 O49 ) nanowire were coated with poly(3-hexylthiophene) (P3HT) and poly(3, 4-ethylenedioxythiophene) (PEDOT) by a radio frequency (RF: 13.56 MHz)-rotating plasma-modification method as alternative counter electrodes for dye-sensitised solar cells (DSSCs). Surface analysis showed the homogenous plasma nanocoating of inorganic nanostructures by P3HT and PEDOT. It was demonstrated that the plasma-modified hybrid platinum-free counter electrodes increased the efficiencies of the DSSCs. The DSSCs based on hybrid nanostructure materials showed a short circuit current density of 9.49, 7.95, 2.59 and 2.57 mAcm −2 for MoS2 /P3HT, MoS2 /PEDOT, W18 O49 /PEDOT and W18 O49 /P3HT samples, respectively. The plasma nanocoating with the nanostructured materials approach for obtaining hybrid counter electrodes in the photovoltaic action shows an alternative route towards cost-effective, green energy conversion.